2018
DOI: 10.1136/bcr-2018-227483
|View full text |Cite
|
Sign up to set email alerts
|

Neck–tongue syndrome

Abstract: Neck–tongue syndrome (NTS) is a rarely reported disorder characterised by paroxysmal episodes of intense pain in the upper cervical or occipital areas associated with ipsilateral hemiglossal dysaesthesia brought about by sudden neck movement. The most likely cause of this clinical entity is a temporary subluxation of the lateral atlantoaxial joint with impaction of the C2 ventral ramus against the articular processes on head rotation. NTS is an under-recognised condition that can be debilitating for patients a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 20 publications
(38 reference statements)
0
5
0
Order By: Relevance
“…Table 2 summarizes the characteristic symptoms of the neck and tongue for NTS and the results of the interventions and treatments. In the six case reports [ 4 , 13 , 15 , 16 , 17 , 18 ], symptoms and treatments were relatively similar. Although patients’ ages were similar, most patients were in their 20s or younger, and the number of women was relatively high.…”
Section: Resultsmentioning
confidence: 98%
“…Table 2 summarizes the characteristic symptoms of the neck and tongue for NTS and the results of the interventions and treatments. In the six case reports [ 4 , 13 , 15 , 16 , 17 , 18 ], symptoms and treatments were relatively similar. Although patients’ ages were similar, most patients were in their 20s or younger, and the number of women was relatively high.…”
Section: Resultsmentioning
confidence: 98%
“…This was suggested by the patient’s self-reported history of cold sores, and consistent with previous research regarding dental manipulation as an etiology of viral Bell’s palsy with trigeminal features [ 7 , 8 ]. We also suspect that the cervical spine played a role in the patient’s symptoms, given previous research showing an association between upper-cervical spine and trigeminal neve symptoms [ 21 , 22 ]. The low-lying cerebellar tonsils in this case were likely an asymptomatic, incidental finding, as this did not meet the threshold for grade 1 Arnold Chiari Syndrome (5 mm below the foramen magnum), and there was no syringomyelia present and no cerebellar signs on examination [ 23 ].…”
Section: Discussionmentioning
confidence: 97%
“…Another study suggested that parasympathetic dysfunction caused by ciliary ganglion ischemia could occasionally result in the mydriatic pupil as a manifestation of GCA [ 12 ]. Chiropractic manipulation and rehabilitation are known to treat neck tongue syndrome [ 13 ], regulate the autonomic nervous system and its projections to the central nervous system [ 14 ]. Similarly, spinal manipulation has biomechanical effects on symptom reduction through muscle relaxation and nerve release [ 15 ].…”
Section: Discussionmentioning
confidence: 99%